2012
DOI: 10.1002/j.1875-9114.2012.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Clopidogrel–Proton Pump Inhibitor Drug Interaction on Adverse Cardiovascular Events in Patients with Acute Coronary Syndrome

Abstract: Study Objective This study examined the effect of clopidogrel and proton pump inhibitors (PPIs) interaction on subsequent acute coronary syndrome (ACS)-related inpatient and emergency room (ER) visits. Design Population based, retrospective cohort study. Data Source IMS LifeLink Health Plan administrative claims database containing a large nationally dispersed group of commercially insured subjects between 2001 and 2008. Patients Subjects age ≥18 years with a diagnosis of ACS and at least one clopidogrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 33 publications
0
17
0
3
Order By: Relevance
“…Less invasive treatments were related with no change, or minimal increase in platelets counts, conversely to the significant increase seen after surgical treatments. The latter might, in part, explain the confounding results of earlier studies of interactions with clopidogrel [24]. Interestingly, the operated patients exhibited the least number of pharmaceuticals in chronic therapy, despite the fact that they had an equal background of ischaemic heart disease.…”
Section: Discussionmentioning
confidence: 96%
“…Less invasive treatments were related with no change, or minimal increase in platelets counts, conversely to the significant increase seen after surgical treatments. The latter might, in part, explain the confounding results of earlier studies of interactions with clopidogrel [24]. Interestingly, the operated patients exhibited the least number of pharmaceuticals in chronic therapy, despite the fact that they had an equal background of ischaemic heart disease.…”
Section: Discussionmentioning
confidence: 96%
“…However, evidence from mechanistic studies has indicated that the anti-platelet effect of clopidogrel is reduced in the presence of PPIs because PPIs inhibit CYP2C19, an enzyme responsible for the conversion of clopidogrel to its active metabolite [6][7][8] . Moreover, several observational studies have shown that concomitant use of clopidogrel and PPIs increases the risk of adverse cardiovascular events [9][10][11][12][13][14][15] . In response to growing concerns over combined use of clopidogrel and PPIs, the US Food and Drug Administration (FDA) issued a public advisory in 2009 advising physicians to re-evaluate the need of PPI use in patients receiving clopidogrel and subsequently a 'black box' warning was added to all clopidogrel (Plavix*) labels in 2011 advising physicians to avoid prescribing clopidogrel and PPIs, namely omeprazole and esomeprazole, simultaneously 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Clopidogrel is a prodrug that is transformed in vivo to an active metabolite by the cytochrome P450 enzyme system [74]. However, some reports have suggested that PPIs interfere with clopidogrel to impair platelet function [23, 24, 75]. PPIs possibly inhibit hepatic cytochrome P450 2C19 (CYP2C19) isoenzyme preventing the conversion of clopidogrel into its active metabolite.…”
Section: Current Therapies For Prevention Of Gastric Damagementioning
confidence: 99%